DIKSI DAN GAYA BAHASA DALAM PIDATO PRESIDEN PRABOWO SUBIANTO - Dirmawati (STKIP Subang, 2026)
This study examines language from a rhetorical perspective, focusing on the use of diction and figures of speech in the speeches of President Prabowo Subianto. The linguistic data were obtained from a collection of President Prabowo Subianto's speech manuscripts, with the researcher serving as the primary research instrument. The findings reveal that President Prabowo Subianto's speeches are predominantly characterized by the use of concrete diction, foreign terms, and popular vocabulary. In addition, the speeches feature regional expressions as well as distinctive lexical choices that reflect his personal rhetorical style. In terms of linguistic aesthetics, the rhetoric is primarily characterized by the use of climactic and simile figures of speech. The use of these rhetorical devices serves to place strong emphasis on the main ideas conveyed. Through these linguistic strategies, President Prabowo Subianto effectively reinforces key messages while capturing the audience's attention throughout his speeches.